Active luminous road markings: A comprehensive review of technologies, materials, and challenges. (11th January 2023) - Lin, Hongwei; Chen, Feng; Zhang, Hongchao
Highlights: The state-of-the-art technologies and research status of different ALRM are reviewed. The development history and status of FRMs are summarized. PPRMs are the leading contender in all ALEMs due to an excellent afterglow intensity and duration. The application and progresses of ELRMs in intelligent traffic control are introduced. Abstract: Road marking is a core part of traffic safety facilities that plays an irreplaceable role in traffic control. With the increasing requirement for road marking, active luminous road markings (ALRMs) have been proposed and have progressed over the years owing to their compelling features of autoluminescence and good recognition. However, there are still some limitations to be further studied, including the luminescence performance, long-term durability, and economic cost. In this study, a comprehensive analysis was conducted to understand the state-of-the-art progress and required future work on ALRMs. Different types of ALRMs were classified, including fluorescent road markings (FRMs), persistent phosphorescent road markings (PPRMs), and electric luminous road markings (ELRMs). Moreover, this paper elaborates on the technical principle, service performance, applications, and existing problems associated with various ALRMs technologies in detail. Furthermore, the challenges and future prospects involved in the development of ALRMs are emphasized to provide avenues and opportunities for future research. It is anticipated that PPRMs and ELRMs, as next-generation road markings, will exhibit the unique advantages of traffic safety improvement, smart traffic control, and an intelligent transportation system.